Cortisol as a Biomarker of Alcohol Use in Combat Veterans: A Literature Review and Framework for Future Research. Issue 3 (2nd July 2020) - Szabo, Yvette Z.; Breeding, Tessa; Hejl, Christina; Guleria, Rakeshwar S.; Nelson, Steven M.; Zambrano-Vazquez, Laura
Abstract: Objective: Alcohol use and alcohol use disorders (AUDs) are an increasing concern among veterans, particularly those from recent conflicts in Iraq and Afghanistan. The study of biomarkers in alcohol use and AUD has moved to enhancing the understanding of the development and maintenance of AUDs, as well as investigating its association with clinical severity and potential predictors of treatment response. Cortisol, a glucocorticoid known as a stress hormone, has been linked with both stress and trauma, as well as increased alcohol suppression effects. Method/Results: The present review summarizes existing literature and presents suggestions for future research to evaluate whether cortisol may be a possible biomarker of alcohol use disorder risk in combat veterans. Specifically, aspects of combat deployments and high levels of PTSD, coupled with the stress of reintegration may dysregulate cortisol and increase risk to AUD. There may also be bidirectional impacts, such that alcohol is used as a coping mechanism and can dysregulate hypothalamic pituitary adrenal (HPA) axis functioning and cortisol. Conclusions: In the context of this framework, cortisol may serve as a biomarker for the development of AUD, as well as a biomarker of risk or relapse. This review ends with both theoretical and clinical implications, as well as directions for future research.